IMPLEMENTATION OF PANEL DATA REGRESSION ON PROFITABILITY SHARIA STOCK IN THE TRADE SUB SECTOR - arisha, bella; Nengsih, Titin Agustin; Willyandari, Nanda Okti; Maulida, Silvi; Susilawati, Susilawati (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2025)
Stocks are certificates that show proof of ownership of a company, and shareholders have claim rights to the company's profits and assets. To measure the company's performance in stocks, several ratios can be used. This study aims to determine the effect of net profit margin (NPM), current ratio (CR), and total asset turnover (TATO) on the profitability (ROA) of Retail Trading companies on the IDX. In this study using descriptive quantitative methods and the analysis used is panel data regression analysis. Panel data regression analysis is used to determine the effect of financial ratios on company profits. The population in the research is 93 companies in the retail trade sub-sector. By using purposive sampling obtained a sampling of 14 companies with a total of 42 samples. The results of this study indicate that the variable current ratio (CR) has a positive effect on return on assets (ROA), while net profit margin (NPM), total asset turnover (TATO) has a negative effect on return on assets (ROA). The model has an effect of 78%, the rest is influenced by other factors outside the research.